An anode chlorine-storing anti-fouling coating material, a preparation method and application thereof
Patent Information
- Application Number
- CN202410875314.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-07-02
AI Technical Summary
[0003]现有技术中,导电防污涂料主要为碳系防污涂料(如碳粉、碳管、石墨烯),和/或金属防污涂料(钛、钨),导电防污涂料主要的工作原理类同电解海水,电解海水过程中通常将上述导电防污涂料涂覆的涂层作为电解阳极,但在电解过程中上述电解阳极会产生大量损耗,存在电解阳极使用寿命短导致防污能力不持久的缺陷,限制了其应用
[0025]进一步地,本发明采用3-(异丁烯酰氧)丙基三甲氧基硅烷作为硅烷偶联剂,硅烷偶联剂将无机导电填料与有机树脂偶联,制备得到硅氧烷丙烯酸树脂;该硅氧烷丙烯酸树脂能够提高导电填料的分散性和稳定性,提高涂料整体导电性和电解能力,进而提高涂料的防污能力。
Smart Images

Figure CN118852939B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of resin material technology, specifically relating to an anodic chlorine storage antifouling coating, its preparation method, and its application. Background Technology
[0002] Marine structures such as ship hulls, offshore platforms, submarines, and harbor facilities are highly susceptible to biofouling (e.g., the attachment of algae, shells, and other marine organisms) in seawater environments. This biofouling not only affects the aesthetics of the structure's surface but also increases fuel consumption, reduces sailing speed, and may accelerate material corrosion. Current technologies typically employ conductive antifouling coatings. The main working principle of these coatings is similar to seawater electrolysis: an insulating and rust-preventive layer is first applied to the water-immersed areas of the hull, followed by a conductive coating. This conductive coating serves as the anode, while other parts of the hull in contact with seawater act as cathodes. A weak current is passed between the electrodes, generating trace amounts (0.05–0.5 ppm) of available chlorine (Cl₂ and ClO₂) approximately 10 μm from the anode. - It can maintain an effective concentration for a short period of time to kill fouling organisms, thereby achieving the purpose of preventing marine biofouling.
[0003] In the existing technology, conductive antifouling coatings are mainly carbon-based antifouling coatings (such as carbon powder, carbon nanotubes, graphene) and / or metal antifouling coatings (titanium, tungsten). The working principle of conductive antifouling coatings is similar to that of seawater electrolysis. In the process of seawater electrolysis, the coating of the above-mentioned conductive antifouling coating is usually used as the electrolysis anode. However, the above-mentioned electrolysis anode will generate a lot of losses during the electrolysis process, resulting in a short service life of the electrolysis anode and a lack of lasting antifouling ability, which limits its application. Summary of the Invention
[0004] The purpose of this invention is to provide an anodic chlorine storage antifouling coating, its preparation method and application. The anodic chlorine storage antifouling coating provided by this invention can reduce electrolytic anode loss and maintain long-lasting antifouling capability.
[0005] To achieve the objectives of this invention, the following technical solutions are provided:
[0006] An anodic chlorine storage antifouling coating, comprising the following raw materials by mass fraction:
[0007] The composition includes 40-50% resin, 10-15% chlorine-storing organic matter, 30-40% organic solvent, 4-6% carbon nanotubes, and 4-5% water.
[0008] The resin includes epoxy resin or siloxane acrylic resin;
[0009] The chlorine-storing organic materials include chlorine-storing silanes or chlorine-storing epoxy resins.
[0010] Preferably, the method for preparing the siloxane acrylic resin includes the following steps:
[0011] The monomer, initiator and organic solvent are mixed and subjected to free radical polymerization to obtain the siloxane acrylic resin;
[0012] The monomers include methyl methacrylate, butyl acrylate, ethyl acrylate, and 3-(isobutenoyloxy)propyltrimethoxysilane.
[0013] Preferably, the molar ratio of methyl methacrylate, butyl acrylate, ethyl acrylate and 3-(isobutenoyloxy)propyltrimethoxysilane in the polymer monomers is 4-5:3-4:1-2:0.5-1.
[0014] Preferably, the molar ratio of the polymerizable monomer to the initiator is 0.9–1.1:0.05–0.07; and the mass ratio of the polymerizable monomer to the organic solvent is 0.9–1.1:0.9–1.1.
[0015] Preferably, the free radical polymerization reaction is carried out at a temperature of 80–90°C for 2–6 hours.
[0016] Preferably, the preparation method of the chlorine-storing epoxy resin includes the following steps:
[0017] 5,5-Dimethylhydantoin, an alcohol solvent, and sodium hydroxide were mixed to carry out a sodium substitution reaction to obtain hydantoin sodium salt.
[0018] The sodium hydantoin and epichlorohydrin are mixed and grafted to obtain the chlorine-storing epoxy resin.
[0019] Preferably, the molar ratio of 5,5-dimethylhydantoin, sodium hydroxide and epichlorohydrin is 0.9-1.1:0.9-1.1:0.9-1.1.
[0020] This invention also provides a method for preparing the anodic chlorine storage antifouling coating described in the above technical solution, comprising the following steps:
[0021] The resin, butyl acetate, chlorine-storing organic matter, ethanol, carbon nanotubes and water are mixed and heat-treated to obtain the anodic chlorine-storing antifouling coating.
[0022] Preferably, the heat treatment temperature is 20–40°C and the time is 1–5 hours.
[0023] The present invention also provides the application of the anodic chlorine storage antifouling coating described in the above technical solution or the anodic chlorine storage antifouling coating prepared by the preparation method described in the above technical solution in the antifouling of marine structures.
[0024] This invention provides an anodic chlorine storage antifouling coating, comprising the following raw materials by mass fraction: 40-50% resin, 10-15% chlorine storage organic matter, 30-40% organic solvent, 4-6% carbon nanotubes, and 4-5% water; wherein the resin includes epoxy resin or siloxane acrylic resin; and the chlorine storage organic matter includes chlorine storage silane or chlorine storage epoxy resin. In the anodic chlorine-storing antifouling coating of this invention, carbon nanotubes are uniformly distributed as the anode in the coating system. When a weak current is applied, the entire anodic chlorine-storing antifouling coating acts as the anode, directly contacting seawater to complete chlorine release. Part of the released chlorine directly kills attached microorganisms; another part oxidizes the stored chlorine organic matter, causing it to be coated with chlorine. Subsequently, it is slowly and uniformly released into the surrounding seawater to continuously drive away and kill attached microorganisms, preventing further fouling. The chlorine release process of the stored chlorine organic matter effectively delays the time of re-electrolysis and effectively delays the problem of wear and tear on the conductive coating that serves as the electrolysis electrode due to over-electrolysis, achieving long-lasting antifouling capability. Furthermore, the anodic chlorine-storing antifouling coating of this invention does not rely on toxic substances that are harmful to the environment and ecology (such as organotin antifouling coatings and copper-based antifouling coatings), greatly reducing its impact on the environment.
[0025] Furthermore, this invention uses 3-(isobutenoyloxy)propyltrimethoxysilane as a silane coupling agent, which couples the inorganic conductive filler with the organic resin to prepare a siloxane acrylic resin. This siloxane acrylic resin can improve the dispersibility and stability of the conductive filler, improve the overall conductivity and electrolytic ability of the coating, and thus improve the antifouling ability of the coating. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 The XRD patterns of 5,5-dimethylhydantoin and hydantoin sodium salt in Example 1 are shown below.
[0028] Figure 2 The XRD patterns of 3-chloropropylethoxysilane and chlorosilane in Example 1 are shown below.
[0029] Figure 3 This is a diagram illustrating the mechanism of action of the anodic chlorine storage coating described in Example 1.
[0030] Figure 4 This is a graph showing the change in chlorine storage per square centimeter at different electrolysis times. Detailed Implementation
[0031] This invention provides an anodic chlorine storage antifouling coating, comprising the following raw materials by mass fraction:
[0032] The composition includes 40-50% resin, 10-15% chlorine-storing organic matter, 30-40% organic solvent, 4-6% carbon nanotubes, and 4-5% water.
[0033] The resin includes epoxy resin or siloxane acrylic resin;
[0034] The chlorine-storing organic materials include chlorine-storing silanes or chlorine-storing epoxy resins.
[0035] In this invention, unless otherwise specified, all raw materials used in the preparation are preferably commercially available products known to those skilled in the art or prepared using methods known to those skilled in the art.
[0036] In this invention, the raw materials for preparing the anodic chlorine storage antifouling coating, by mass fraction, include 40-50% resin, preferably 45-48%. In this invention, the resin includes epoxy resin or siloxane acrylic resin; the epoxy resin is preferably E-44 (6101) epoxy resin, sourced from Dingyuan County Danbao Resin Co., Ltd.
[0037] In this invention, the preparation method of the siloxane acrylic resin preferably includes the following steps:
[0038] The monomer, initiator and organic solvent are mixed and subjected to free radical polymerization to obtain the siloxane acrylic resin;
[0039] The monomers include methyl methacrylate, butyl acrylate, ethyl acrylate, and 3-(isobutenoyloxy)propyltrimethoxysilane.
[0040] This invention involves mixing monomers, an initiator, and an organic solvent to conduct a free radical polymerization reaction, thereby obtaining the siloxane acrylic resin. In this invention, the molar ratio of methyl methacrylate, butyl acrylate, ethyl acrylate, and 3-(isobutyryloxy)propyltrimethoxysilane in the monomers is preferably 4–5:3–4:1–2:0.5–1, more preferably 5:3.5:1:0.5. In this invention, the initiator preferably includes one of azobisisobutyronitrile, benzoyl peroxide, and azobisisoheptanenitrile, more preferably azobisisobutyronitrile; the organic solvent preferably includes one of butyl acetate, ethyl acetate, ethanol, and isopropanol, more preferably butyl acetate.
[0041] In this invention, the molar ratio of the polymerizable monomer to the initiator is preferably 0.9-1.1:0.05-0.07, more preferably 1:0.06; the mass ratio of the polymerizable monomer to the organic solvent is 0.9-1.1:0.9-1.1, more preferably 1:1.
[0042] In this invention, it is preferable to first dissolve the initiator in a portion of an organic solvent to obtain an initiator solution;
[0043] The first part of the initiator solution, the remaining organic solvent and part of the polymerizable monomers are mixed to carry out the initiation reaction to obtain the initiation reaction system;
[0044] The remaining monomers and the second part of the initiator solution are mixed with the initiation reaction system to carry out the first free radical polymerization reaction, thereby obtaining the first polymerization system;
[0045] The remaining initiator solution and the second initiation system are mixed to carry out a second free radical polymerization reaction to obtain the siloxane acrylic resin.
[0046] In this invention, the volume ratio of the partial organic solvent to the remaining organic solvent is preferably 1-3:7-9, more preferably 2:8; the volume ratio of the first partial initiator solution, the second partial initiator solution, and the remaining initiator solution is preferably 1-3:6-8:1-2, more preferably 2:7:1; the mass ratio of the partial polymerizable monomer to the remaining polymerizable monomer is preferably 1-3:7-9, more preferably 2:8.
[0047] In this invention, the temperatures of the initiation reaction, the first free radical polymerization reaction, and the second free radical polymerization reaction are preferably 80-90°C, more preferably 85°C; the time of the initiation reaction is preferably 0.5-1 h; the time of the first free radical polymerization reaction is preferably 2-3 h; and the time of the second free radical polymerization reaction is preferably 1-2 h.
[0048] In this invention, the raw materials for preparing the anodic chlorine-storing antifouling coating, by mass fraction, include 10-15% chlorine-storing organic matter, preferably 12-13%. In this invention, the chlorine-storing organic matter includes chlorine-storing silanes or chlorine-storing epoxy resins. In this invention, when the resin is preferably an epoxy resin, the chlorine-storing organic matter is a chlorine-storing epoxy resin; when the resin is preferably a siloxane acrylic resin, the chlorine-storing organic matter is a chlorine-storing silane.
[0049] In this invention, the method for preparing the chlorinated silane preferably includes the following steps:
[0050] 5,5-Dimethylhydantoin, an alcohol solvent, and sodium hydroxide were mixed to carry out a sodium substitution reaction to obtain hydantoin sodium salt.
[0051] The sodium hydantoin, N,N-dimethylformamide, and 3-chloropropylethoxysilane were mixed and subjected to a substitution reaction to obtain the chlorosilane.
[0052] This invention involves mixing 5,5-dimethylhydantoin, an alcohol solvent, and sodium hydroxide to conduct a sodium substitution reaction, yielding sodium hydantoin. In this invention, the alcohol solvent is preferably ethanol; the preferred molar ratio of 5,5-dimethylhydantoin, sodium hydroxide, and alcohol solvent is 0.09–0.11 mol:0.09–0.11 mol:90–110 mL, more preferably 0.1 mol:0.1 mol:100 mL. In this invention, the preferred temperature for the sodium substitution reaction is 80–90°C, more preferably 85°C, and the preferred time is 0.5–2 h. In this invention, after the sodium substitution reaction, solvent removal and drying are preferably performed sequentially; the preferred method for solvent removal is rotary evaporation; the preferred drying temperature is 40–80°C, more preferably 60°C, and the preferred time is 12–48 h, more preferably 24 h; the drying is preferably carried out under vacuum conditions.
[0053] After obtaining sodium hydantoin, the present invention mixes the sodium hydantoin, N,N-dimethylformamide, and 3-chloropropylethoxysilane for a grafting reaction to obtain the chlorosilane. In the present invention, the preferred molar ratio of sodium hydantoin, 3-chloropropylethoxysilane, and N,N-dimethylformamide is 0.09–0.11 mol:0.09–0.11 mol:90–110 mL, more preferably 0.1 mol:0.1 mol:100 mL. In the present invention, the preferred temperature for the grafting reaction is 95–105 °C, more preferably 100 °C, and the preferred time is 7–12 h, more preferably 8–10 h. In the present invention, after the grafting reaction, it is preferable to sequentially perform filtration, solvent removal, and drying; the solvent removal and drying are preferably the same as those described above, and will not be repeated here. The present invention removes the sodium chloride precipitate produced by the grafting reaction by filtration.
[0054] In this invention, the preparation method of the chlorine-storing epoxy resin preferably includes the following steps:
[0055] 5,5-Dimethylhydantoin, an alcohol solvent, and sodium hydroxide were mixed to carry out a sodium substitution reaction to obtain hydantoin sodium salt.
[0056] The sodium hydantoin and epichlorohydrin are mixed and grafted to obtain the chlorine-storing epoxy resin.
[0057] This invention involves mixing 5,5-dimethylhydantoin, an alcohol solvent, and sodium hydroxide to perform a sodium substitution reaction, yielding hydantoin sodium salt. In this invention, the alcohol solvent is preferably isopropanol. The preparation of the hydantoin sodium salt is preferably consistent with the preparation of the hydantoin sodium salt described above, and will not be repeated here.
[0058] After obtaining sodium hydantoin, the present invention mixes the sodium hydantoin with epichlorohydrin and performs a grafting reaction to obtain the chlorine-storing epoxy resin. In the present invention, the molar ratio of 5,5-dimethylhydantoin to epichlorohydrin is preferably 0.09–0.11:0.09–0.11, more preferably 0.1:0.1. In the present invention, the grafting reaction temperature is preferably 80–90°C, more preferably 85°C, and the time is preferably 2–4 hours, more preferably 3 hours.
[0059] In this invention, after the grafting reaction, it is preferable to perform filtration, solvent removal and drying in sequence; the solvent removal and drying are preferably the same as those described above, and will not be repeated here.
[0060] In this invention, the raw materials for preparing the anodic chlorine storage antifouling coating, by mass fraction, include 30-40% organic solvent, more preferably 34-36%. In this invention, the organic solvent is preferably the same as described above. In this invention, when the resin is preferably a siloxane acrylic resin, the organic solvent is butyl acetate and ethanol; the mass ratio of butyl acetate to ethanol is preferably 20-25:12-13, more preferably 22-23:12-13. When the resin is preferably an epoxy resin, the organic solvent is isopropanol. In this invention, when the resin is a siloxane acrylic resin, the organic solvent can promote a certain degree of hydrolysis and condensation between some of the siloxanes in the resin and the siloxanes in the chlorine storage silane, resulting in a long-term uniform and stable coating system; when the resin is an epoxy resin, because epoxy resin is too viscous to disperse the conductive filler (carbon nanotubes), isopropanol is used for dilution.
[0061] In this invention, the raw materials for preparing the anodic chlorine storage antifouling coating, by mass fraction, include 4-6% carbon nanotubes, preferably 5%. In this invention, the carbon nanotubes are preferably multi-walled carbon nanotubes or high-purity hydroxylated multi-walled carbon nanotubes; the multi-walled carbon nanotubes are preferably 95% or 99% multi-walled carbon nanotubes. In this invention, the carbon nanotubes can form conductive pathways in the coating, which is the basis for the electrolytic chlorine removal of the coating.
[0062] In this invention, the raw materials for preparing the anodic chlorine storage antifouling coating include 4-5% water, preferably 4.5%, by mass fraction. In this invention, the water is preferably deionized water.
[0063] This invention also provides a method for preparing the anodic chlorine storage antifouling coating described in the above technical solution, comprising the following steps:
[0064] The resin, butyl acetate, chlorine-storing organic matter, ethanol, carbon nanotubes and water are mixed and heat-treated to obtain the anodic chlorine-storing antifouling coating.
[0065] In this invention, it is preferable to first mix resin, butyl acetate, chlorine-storing organic matter, ethanol, and water to obtain a gel system; then mix the gel system with carbon nanotubes and perform heat treatment to obtain the anodic chlorine-storing antifouling coating. In this invention, it is preferable to adjust the pH value of the gel system to 2-4, more preferably 3.5-4; the preferred reagent for adjusting the pH is acetic acid.
[0066] In this invention, the heat treatment temperature is preferably 20–40°C, more preferably 30–35°C, and the time is preferably 1–5 h, more preferably 2–4 h. This invention promotes the hydrolysis-condensation reaction of siloxanes in the resin and the stored chlorine silane through heat treatment, resulting in partial bonding between the resin and the stored chlorine silane, thus maintaining long-term uniformity and stability.
[0067] In this invention, after obtaining the anodic chlorine storage antifouling coating, the anodic chlorine storage antifouling coating can be dried to obtain a solid anodic chlorine storage antifouling coating; the drying is preferably the same as the drying described above.
[0068] The present invention also provides the application of the anodic chlorine storage antifouling coating described in the above technical solution or the anodic chlorine storage antifouling coating prepared by the preparation method described in the above technical solution in the antifouling of marine structures.
[0069] In this invention, the marine structures preferably include ship hulls, offshore platforms, submarines, or harbor facilities.
[0070] In this invention, when the anodic chlorine-storing antifouling coating is applied to marine structures for antifouling, the applied weak current is preferably 2 to 4V, more preferably 3V.
[0071] To further illustrate the present invention, the following detailed description, in conjunction with the accompanying drawings and embodiments, describes the anodic chlorine storage antifouling coating, its preparation method, and its application, but these descriptions should not be construed as limiting the scope of protection of the present invention.
[0072] Example 1
[0073] Methyl methacrylate, butyl acrylate, ethyl acrylate and 3-(isobutyryloxy)propyltrimethoxysilane were weighed and mixed in a molar ratio of 5:3.5:1:0.5 to obtain the polymerizable monomers.
[0074] Weigh out azobisisobutyronitrile and butyl acetate according to a molar ratio of monomer to azobisisobutyronitrile of 1:0.06 and a mass ratio of monomer to butyl acetate of 1:1, and set aside.
[0075] Azobisisobutyronitrile was dissolved in a portion of butyl acetate (accounting for 20% of the total volume of butyl acetate) to obtain an azobisisobutyronitrile solution.
[0076] A portion of the azobisisobutyronitrile solution (accounting for 20% of the total volume of the azobisisobutyronitrile solution), the remaining butyl acetate, and a portion of the polymerizable monomers (accounting for 20% of the total mass of the polymerizable monomers) were placed in a four-necked flask and the reaction was initiated at 85°C in an oil bath for 0.5 h to obtain the initiation reaction system.
[0077] The remaining monomers and a portion of the azobisisobutyronitrile solution (accounting for 10% of the total volume of the azobisisobutyronitrile solution) were added dropwise to the above initiation reaction system using a peristaltic pump. The free radical polymerization reaction was carried out for 1 hour under an oil bath at 85°C. Then, the remaining azobisisobutyronitrile solution was added, and the reaction was continued for another hour to obtain the siloxane acrylic resin.
[0078] 0.1 mol of 5,5-dimethylhydantoin was dissolved in 100 mL of ethanol, and 0.1 mol of sodium hydroxide was added. The mixture was refluxed at 80 °C for 2 h. The solvent was removed by rotary evaporation, and the residue (in foam form) was vacuum dried at 60 °C for 12 h to obtain sodium hydantoin.
[0079] The above-mentioned sodium hydantoin was dissolved in 100 mL of N,N-dimethylformamide, and 0.1 mol of 3-chloropropylethoxysilane was added dropwise. The mixture was reacted at 100 °C for 8 h. The sodium chloride precipitate was removed by filtration, and the solvent was removed by rotary evaporation of the filtrate. The resulting yellow viscous substance was chlorosilane.
[0080] Weigh out 20g of the above-mentioned siloxane acrylic resin, 10g of butyl acetate, 5g of the above-mentioned chlorine-storing silane, 6g of anhydrous ethanol and 2.5g of water and mix them to obtain a gel system. Adjust the pH of the gel system to 3.5 with acetic acid, then add 2.61g of multi-walled carbon nanotubes and stir for 5h in a 40℃ water bath to obtain the anodic chlorine-storing coating.
[0081] Figure 1 The XRD patterns of 5,5-dimethylhydantoin and hydantoin sodium salt in Example 1 are shown below. Figure 1 It is known that the present invention successfully replaced one NH bond in 5,5-dimethylhydantoin with sodium ions, which prepares for the subsequent introduction of the other NH bond in the sodium hydantoin salt into the siloxane system.
[0082] Figure 2 The XRD patterns of 3-chloropropylethoxysilane and chlorosilane in Example 1 are shown below. Figure 2 It is known that by grafting hydantoin sodium salt with 3-chloropropyltriethoxysilane, the remaining NH bond in the hydantoin sodium salt will be introduced into the siloxane system, preparing for the introduction of the NH bond into the coating.
[0083] Figure 3 This is a schematic diagram illustrating the mechanism of action of the anodic chlorine storage coating described in Example 1. In this example, the coating is directly electrolyzed using seawater as the electrolyte. Under the influence of the anodic current, the Cl- in the seawater...- The discharge generates Cl2, which reacts with H2O to produce HClO. Part of this HClO is directly used to kill marine larvae and spores. Building upon this, N-halogen amine compounds are introduced into the coating. N-halogen amines are organic compounds containing one or more N×(X, where X is Cl, Br, or I) covalent bonds, formed by the reaction of precursor compounds containing amine, amide, or imide groups with an oxidizing agent (such as hypochlorite). Another portion of the HClO oxidizes the NH bonds introduced into the coating, transforming them into N-Cl covalent bonds. During the sterilization process, the N-Cl bonds release highly oxidizing Cl-. + It damages the cell membrane, enters the microorganism, interferes with the activity of cellular enzymes and metabolic processes, thereby leading to bacterial death. + During contact with bacteria, the N-Cl bonds are consumed, transforming into NH bonds and losing their bactericidal properties. However, upon further treatment with a hypohalite solution (hypochlorous acid solution), the hypohalite can oxidize the NH bonds again into NX bonds, which can exert a bactericidal effect. Therefore, this coating has direct bactericidal and long-lasting antibacterial effects, as well as antibacterial regenerability.
[0084] Example 2
[0085] 0.1 mol of 5,5-dimethylhydantoin was dissolved in 100 mL of isopropanol, and 0.1 mol of sodium hydroxide was added. The sodium substitution reaction was carried out at 85 °C for 2 h. Then, 0.1 mol of epichlorohydrin was added dropwise over 0.5 h, and the reaction was continued at 85 °C for 3 h. The sodium chloride precipitate was removed by filtration, and the solvent was removed by rotary evaporation. The resulting light yellow liquid was vacuum dried at 60 °C for 12 h to remove the solvent. The upper transparent viscous liquid was obtained as the chlorine-storing epoxy resin.
[0086] 20g of epoxy resin, 20g of isopropanol, 5g of the above-mentioned chlorine-storing epoxy resin and 2.25g of multi-walled carbon nanotubes were mixed and stirred at room temperature (30°C) for 2 hours to obtain epoxy anode chlorine-storing coating.
[0087] Test Example 1
[0088] The anodic chlorine storage coating described in Example 1 was applied to a 75×25mm area. 2 The epoxy sheets were dried completely in an oven and placed upright in a cubic electrolytic cell. A 3.5 wt% NaCl solution was added, 25 mm above the bottom of the cell, forming an electrolysis zone of 25 × 25 mm. 2Electrolysis was performed at 2V for 10 min, 15 min, 20 min, 25 min, and 30 min, respectively. The oxidized chlorine content on the coating surface was determined by iodometric titration. The epoxy sheet coated with the anodic chlorine storage coating described in Example 1 was added to an excess of KI in a conical flask containing 20 mL of distilled water and thoroughly mixed. Five drops of 0.5 wt% starch solution were added as an indicator, and titration was performed with 0.001 N Na₂S₂O₃ solution until the titration endpoint. Calculations were performed according to Formula I:
[0089] Cl(%)=(c×V×35.45) / 2m×100 Formula I;
[0090] In Formula I, c is the concentration of sodium thiosulfate (mg / L); V is the volume of sodium thiosulfate (L); and m is the area of the sample being tested (cm²). 2 );
[0091] Figure 4 This is a graph showing the change in chlorine storage per square centimeter at different electrolysis times, from... Figure 4 It can be seen that the chlorine content increases with the increase of electrolysis time. Considering the effects of electrolysis time on anode life and the influence of chlorine content on the electrolysis time, an electrolysis time of 15 min is selected.
[0092] Test Example 2
[0093] The specific steps for testing the release performance after chlorine electrolysis are as follows:
[0094] After electrolysis for 15 minutes, the epoxy sheet coated with the anodic chlorine storage coating described in Example 1 was immersed in 20 mL of 3.5 wt% sodium chloride solution. Every 1 hour, the epoxy sheet was taken out and placed into another 20 mL of 3.5 wt% sodium chloride solution for titration. The effective chlorine release rate in the solution was measured, and the results are shown in Table 1.
[0095] Table 1. Test results of the chlorine release performance of the anodic chlorine storage coating described in Example 1 after electrolytic chlorine storage.
[0096]
[0097] Note: In Table 1, "**" indicates the subsequent omitted detection time (18-24h). The detection process of this invention is to detect once per hour until the coating no longer releases chlorine into the water, which is recorded as the release time, i.e. the effective time after the coating electrolyzes and stores chlorine.
[0098] As shown in Table 1, the available chlorine is released at a uniform rate, and the water layer on the coating surface can reach 0.133 ppm (>0.05). The effective chlorine release and antifouling time is 16 to 21 hours.
[0099] Table 2. Test results of the chlorine release performance of the anodic chlorine storage coating described in Example 2 after electrolytic chlorine storage.
[0100]
[0101] Note: In Table 2, "**" indicates the subsequent omitted detection time (18-24h). The detection process of this invention is to detect once per hour until the coating no longer releases chlorine into the water, which is recorded as the release time, i.e. the effective time after the coating electrolyzes and stores chlorine.
[0102] As shown in Table 2, the available chlorine is released at a uniform rate, and the water layer on the coating surface can reach 0.138 ppm (>0.05). The effective chlorine release and antifouling time is 15 to 17 hours.
[0103] Test Example 3
[0104] The antifouling performance of the chlorine storage coating on the anode after electrolysis was tested, and the specific steps were as follows:
[0105] The antibacterial activity of the chlorine-storing coating was evaluated using Staphylococcus aureus (ATCC 43300), a Gram-positive bacterium, and Escherichia coli (ATCC 25922), a Gram-negative bacterium. Bacterial cultures were performed using broth and nutrient agar media. All instruments were sterilized and kept dry before use.
[0106] Activating bacteria: Inoculate the bacterial strain preserved at 4℃ into 50mL of nutrient broth and incubate at 37℃ for 20–24 hours. Dilute the cultured bacteria with nutrient broth to prepare a bacterial suspension with a concentration of 10. 8 The bactericidal performance was analyzed using the plate count method with CFU / mL.
[0107] The epoxy sheet coated with the anodic chlorine storage coating described in Example 1 was immersed in 15 mL of the above-mentioned bacterial solution after electrolysis. The bacterial concentration on the sheet and in the immersed bacterial solution was measured every 4 hours. 7 mL of physiological saline was taken from the sheet to elute the bacterial suspension on the coating several times and collected. The eluent was used for plate colony counting, with a bacterial gradient of 10. -3 10 -4 10 -5 The bacteria were incubated at 37°C for 16 hours on solid culture medium. The antibacterial efficiency at different inactivation times was calculated based on the number of colonies. The results are shown in Tables 2 and 3.
[0108] Table 3. Test results of the antifouling performance of the anodic chlorine storage coating described in Example 1 after electrolytic chlorine storage.
[0109]
[0110]
[0111] Table 4. Test results of the antifouling performance of the anodic chlorine storage coating described in Example 1 after electrolytic chlorine storage.
[0112] 4h 186 280 33.57% 196 282 30.50% 8h 131 286 54.20% 150 273 45.05% 12h 108 296 63.51% 93 287 67.60% 16h 83 324 74.38% 77 335 77.01% 20h 39 436 91.06% 24 428 94.39%
[0113] As shown in Tables 3 and 4, after chlorination treatment in seawater at 2V for 15 minutes, the coating exhibited an inhibition rate of over 70% against the selected Escherichia coli and Staphylococcus aureus within 20 hours. Immersing the chlorinated coating in the bacterial solution further increased the bacterial kill rate over time, indicating that the effective chlorine in the coating was gradually released into the surrounding liquid environment to kill bacteria and inhibit further bacterial adhesion to the coating surface. Therefore, this coating can effectively prevent fouling.
[0114] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An anodic chlorine storage antifouling coating, characterized in that, The raw materials for preparation, by mass fraction, are: The composition includes 40-50% resin, 10-15% chlorine-storing organic matter, 30-40% organic solvent, 4-6% carbon nanotubes, and 4-5% water. The resin includes a siloxane acrylic resin; the preparation method of the siloxane acrylic resin includes the following steps: The monomer, initiator and organic solvent are mixed and subjected to free radical polymerization to obtain the siloxane acrylic resin; The monomers include methyl methacrylate, butyl acrylate, ethyl acrylate, and 3-(isobutenoyloxy)propyltrimethoxysilane; the molar ratio of methyl methacrylate, butyl acrylate, ethyl acrylate, and 3-(isobutenoyloxy)propyltrimethoxysilane in the monomers is 4~5:3~4:1~2:0.5~1; the molar ratio of the monomers to the initiator is 0.9~1.1:0.05~0.07; and the mass ratio of the monomers to the organic solvent is 0.9~1.1:0.9~1.
1. The chlorine-storing organic compound is a chlorine-storing silane; the preparation method of the chlorine-storing silane includes the following steps: 5,5-Dimethylhydantoin, an alcohol solvent, and sodium hydroxide are mixed to carry out a sodium substitution reaction to obtain sodium hydantoin; the ratio of 5,5-dimethylhydantoin, sodium hydroxide, and alcohol solvent is 0.09~0.11 mol:0.09~0.11 mol:90~110 mL. The sodium hydantoin salt, N,N-dimethylformamide, and 3-chloropropylethoxysilane were mixed and subjected to a substitution reaction to obtain the chlorosilane; the molar ratio of sodium hydantoin, 3-chloropropylethoxysilane, and N,N-dimethylformamide was 0.09~0.11 mol:0.09~0.11 mol:90~110 mL. The organic solvent is butyl acetate and ethanol.
2. The anodic chlorine storage antifouling coating according to claim 1, characterized in that, The free radical polymerization reaction is carried out at a temperature of 80-90℃ for 2-6 hours.
3. The method for preparing the anodic chlorine storage antifouling coating according to claim 1 or 2, characterized in that, Includes the following steps: The resin, butyl acetate, chlorine-storing organic matter, ethanol, carbon nanotubes and water are mixed and heat-treated to obtain the anodic chlorine-storing antifouling coating.
4. The preparation method according to claim 3, characterized in that, The heat treatment is performed at a temperature of 20-40°C for 1-5 hours.
5. The application of the anodic chlorine-storing antifouling coating according to claim 1 or 2 or the anodic chlorine-storing antifouling coating prepared by the preparation method according to claim 3 or 4 in the antifouling of marine structures.
Citation Information
Patent Citations
Verdelite electrolyzed antifouling paint of sea water and method of producing the same
CN101402813A
Synthesizing method for flame retardant type glycolylurea epoxide resin
CN101624439A
Halogenoamine modified active charcoal used for indoor sterilization and preparation method thereof
CN108513987A